Revitalizing Religious Practice among Muslim Youth - Fakhrurrozi Pardosi; Fatih Insani (Al-Arkhabiil)
This community service project aimed to explore the religious practices of Muslim youth in Latak Ayah Village, Simeulue Cut District, Simeulue Regency. The initiative addressed the irregular performance of five daily prayers and fasting among adolescents, particularly focusing on revitalizing awareness and commitment through targeted religious interventions. Using qualitative methods, the team conducted interviews with community leaders, organized training on basic Islamic rituals, and facilitated halaqah (study circles). The intervention involved 30 youths and engaged five local religious figures. The outcomes showed increased parental involvement in guiding children’s worship and improved motivation among early adolescents to participate in congregational prayers. Key challenges included limited religious institutions and financial constraints, which were addressed through collaborations with local da’wah groups and philanthropic organizations. This study provides insight into effective grassroots approaches to enhance youth religiosity in remote Muslim communities.